2006
DOI: 10.1063/1.2361081
|View full text |Cite
|
Sign up to set email alerts
|

Band gap properties of Zn1−xCdxO alloys grown by molecular-beam epitaxy

Abstract: Optical absorption and reflectance measurements are performed to evaluate compositional and temperature dependences of band gap energies of Zn1−xCdxO alloys grown by molecular-beam epitaxy. The compositional dependence of the band gap energy, determined by taking into account excitonic contributions, is shown to follow the trend Eg(x)=3.37−2.82x+0.95x2. Incorporation of Cd was also shown to somewhat slow down thermal variation of the band gap energies, beneficial for future device applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 18 publications
2
34
6
Order By: Relevance
“…However, when using the band bowing parameters reported by Wang and co-workers [27] we find that this observed minimum of the band gap is higher than expected from the observed Cd concentration. Indeed, a composition of x ≈ 0.23 should give E g ≈ 2.77 eV.…”
Section: Resultscontrasting
confidence: 41%
See 1 more Smart Citation
“…However, when using the band bowing parameters reported by Wang and co-workers [27] we find that this observed minimum of the band gap is higher than expected from the observed Cd concentration. Indeed, a composition of x ≈ 0.23 should give E g ≈ 2.77 eV.…”
Section: Resultscontrasting
confidence: 41%
“…The samples were investigated using Xray diffraction, and were found to be single phase wurtzite with no indication of rs-CdO. The band gap of the alloy can be tuned as a function of the Zn/Cd ratio [26][27][28], e.g. for compositions Zn 1−x Cd x O, x=0-0.67 the band gap was found to vary between 3.25 and 1.7 eV [29].…”
Section: Experimental Setup and Data Analysismentioning
confidence: 99%
“…But, the curve by eq. (4) is different with the shape obtained by other researchers [23][24][25]. Only, the bandgap energies reported by Makino et al [23] is close to our values at low composition rates below 0.13 as shown in figure 8.…”
Section: Resultssupporting
confidence: 48%
“…At this time, the bowing parameter was estimated to be 2.3582 eV. For this b value, Makino et al [23] obtained 5.93 eV utilizing absorption measurement, Wang et al [24] found 0.95 eV using reflectance measurement, and Gruber et al [25] reported 8.14 eV employing photoluminescence measurement. However, our value is similar to the value, b=2.5 eV, obtained by the ternary compound of AlInN [26].…”
Section: Resultsmentioning
confidence: 99%
“…The ZnO (hexagonal) and CdO (cubic) have very different crystal structure, and also, low thermodynamic solubility (~ 2 mol.%) of CdO in CdO-ZnO system make it very difficult to grow single-phase hexagonal Cd x Zn 1−x O thin films with high Cd concentration (Ishihara et al 2006). Different methods can be employed to grow mixed Cd x Zn 1−x O thin films, such as molecular beam epitaxy (Wang et al 2006), sputtering (Ma et al 2011), pulsed laser deposition (Makino et al 2013) and spray pyrolysis (Vijayalakshmi et al 2008). Compared to different methods, the spray pyrolysis method is simplest industrially applicable method to produce metal oxide thin films.…”
Section: Introductionmentioning
confidence: 99%